(untitled) (Gestão & Regionalidade, 2015)
This research seeks to verify the existence of different configurations in the process of strategy formation in micro and small companies in the city of Londrina (PR), Brazil. The theoretical framework addresses their environmental context, the type of their strategy, the entrepreneur potential and their forms of development. Research approach is defined as quantitative and descriptive, characterized as a survey in 219 organizations from Londrina (PR). The results indicate that the local environment is the dominant strategic profile of these companies, and they are constantly analyzing their operating environment to develop new concepts. Similarities in most strategic configurations are observed when the profile of the companies is analyzed. The main difference found in the strategy adopted by trade companies and industry that differs from the service companies is: while trade companies and industry are more cautious and stable, service companies are more daring.